A proposal for the development of the PNOC library into an information center a five-year program - Martin, Carmelita M.; Buenrostro, Juan Jr. C.; Hidalgo, Namnama P.
The Philippine National Oil Company is one of the country's largest and most important corporations. It plays a major role in the development of the Philippine economy because it is tasked with the maintenance of a reliable supply of energy for the country. To help the Company in pursuing its mandated objectives, it is important that its requirements for information services be adequately met. Unfortunately, the present Library does not have the capabilities to provide the needed information services. It is for this reason that this study of a plan for the transformation of the PNOC Library into an Information Center has been made.
The following methods were employed to obtain the necessary baseline data: documentary analysis, needs assessment survey using a structured questionnaire, interviews, correspondence and visits to other libraries and information centers. The survey findings showed that there is a need to: 1) improve the information services of the library to include abstracting service and current awareness services; 2) acquire more publications on topics recommended by the respondents; 3) conduct a user education to orient the user in the availability of resources, services and facilities in the library; and, 4) conduct a user study to update user profiles and determine the kind of information services still needed.
The results of the study show that there is a need to transform the present PNOC Library into an information center in order to meet the increasing demands of the user community for more and better information services.
A five-year development plan for such transformation has been drawn up for maximum efficiency and effectiveness. This plan includes the definition of the policy, scope, objectives and functions of the proposed PNOC Information Center. It also describes the information services to be offered. This includes the current awareness service such as SDI and Current Contents. Further, it identifies the various resources needed such as manpower, budget allocations and publications to implement these services. A timetable for plan implementation has been included to serve as a guide in the implementation of the five-year development plan.
Typescript.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Philippine National Oil Company Library; Philipppine National Oil Company -- Information services